Impact of augmented reality virtual try-on applications on customer sentiment - Kirvesmäki, Miisa (2025)
The purpose of this master’s thesis is to examine the impact of virtual try-on MAR applications on customer sentiment. Despite the continuous development and growth of eCommerce, online shopping is challenged with the inability to try-on items. As a result, a promising solution called mobile augmented reality (MAR) has emerged with the aim of solving this problem. These MAR applications focus to solve common online shopping issues related to product fitting, such as selecting the right size or desired fit. MAR has the potential of improving the profitability and sustainability of eCommerce through decreased product returns and increased conversion rates. This study aims to examine the impact of virtual try-on MAR applications on customer sentiment and identify possible differences in customer satisfaction across different product categories. The research analyses customer reviews using a lexicon-based sentiment analysis method called VADER. The customer reviews are collected from Apple App Store across three product categories: apparel, furniture, and beauty. As a result, this study discovers that MAR applications significantly enhance customer satisfaction and engagement, as the majority of reviews analysed are positive. The main factors behind positive reviews were the fun and entertainment value of the applications, ease of use, and the realistic experience they provided. The findings also suggest that user sentiment is not uniform across all MAR applications but is shaped by the application category and user expectations. Among the three categories examined, user comments were most positive within the apparel applications, followed by furniture and lastly beauty applications. This indicates that MAR technology is particularly effective in improving customer satisfaction in the apparel industry, where virtual try-ons can significantly reduce uncertainty related to online shopping and enhance the shopping experience. The findings from this study can help businesses prioritize areas for improvement and design targeted strategies for MAR deployment to enhance customer satisfaction.